Screening of antioxidant and anti-inflammatory activities among thiopyrano[2,3-d]thiazoles - Lozynskyi, A.V.; Kaminskyy, D.V.; Romanchyshyn, Kh.B.; Semenciv, N.G.; Ogurtsov, V.V.; Nektegayev, I.O.; Lesyk, R.B. (Вiopolymers and Cell, 2015)
The aim of present research was the investigation of antioxidant and antiexudative activities of the series of thiopyrano[2,3-d]thiazoles synthesized based on cinnamic acid amides. Methods. Organic synthesis; spectral methods; free radical scavenging assay (DPPH test); evaluation of antiexudative activity (carrageenan oedema model in rats). Results. The evaluation of the free radicals scavenging activity and antiexudative activity of series of the 2-oxo-5-phenyl-7-aryl(hetaryl)-3,7-dihydro-2H-thiopyrano[2,3-d]thiazole-6-carboxylic acid amides was performed. Among the tested compounds, rel-(5R,6S,7S)-N-(4-methylphenyl)-7-(4-methylphenyl)-2-oxo-5-phenyl-3,5,6,7-tetrahydro-2H-thiopyrano[2,3-d]thiazole-6-carboxamide possessed the highest level of both activities. The experimental data most probably indicate a pronounced effect of methyl groups (phenyl fragments) on the realization of the anti-inflammatory and antioxidant effects and allow a suggestion about the antiradical mechanism of anti-inflammatory activity of the target compounds. Conclusions. The anti-inflammatory and free radicals scavenging activities of some tiopyrano[2,3-d]thiazoles have been established and the most active compounds were identified. Some findings of the structure-activity relationship were set up. Мета даного дослідження полягала у вивченні антиоксидантної та антиексудативної активності похідних тіопірано [2,3-d]тіазолу одержаних на основі амідів коричної кислоти. Методи. Органічний синтез; спектральні методи; оцінка радикал поглинаючої (DPPH тест) та антиексудативної активностей (карагенінової модель набряку лапи щура). Результати. Проведено визначення радикал поглинаючої та антиексудативної активності амідів 2-оксо-5-феніл-7-арил(гетерил)-3,7-дигідро-2Н-тіопірано[2,3-d]тіазол-6-карбонових кислот. Серед тестованих сполук rel-(5R,6S, 7S)-N-(4-метилфеніл)-7-(4-метилфеніл)-2-оксо-5-феніл-3,5,6,7-тетрагідро-2H-тіопірано[2,3-d]тіазол-6-карбоксамід характеризувався максимальними значеннями обох видів активності. Отримані дані, очевидно, свідчать про виражений вплив метильних груп (у фенільних фрагментах) на реалізацію протизапального та антиоксидантного ефектів та дозволяють припустити антирадикальний механізм протизапальної активності сполук даного ряду. Висновки. Встановлено протизапальну та антирадикальну активності ряду тіопірано[2,3-d]тіазолів, ідентифіковано сполуки з високим рівнем активності та проаналізовані деякі аспекти взаємозв’язку структура-активність. Цель данного исследования заключалась в изучении антиоксидантной и антиэкссудативной активности производных тиопирано[2,3-d]тиазола полученых на основе амидов коричной кислоты. Методы. Органический синтез; спектральные методы; оценка радикал поглощающей (DPPH тест) и антиэкссудативной активностей (карагениновая модель отека лапы крысы). Результаты. Проведено исследование радикал поглощающей активности и антиэкссудативного активности амидов 2-оксо-5-фенил-7-арил(гетерил)-3,7-дигидро-2Н-тиопирано[2,3-d]тиазол-6-карбоновых кислот. Среди испытуемых соединений rel-(5R,6S,7S)-N-(4-метилфенил)-7-(4-метилфенил)-2-оксо-5-фенил-3,5,6,7-тетрагидро-2H-тиопирано[2,3-d]тиазол-6-карбоксамид характеризировался максимальными значениями обоих видов активности. Полученные данные, по-видимому, свидетельствуют о выраженном влиянии метильных групп (в фенильных фрагментах) на реализацию противовоспалительного и антиоксидантного эффектов и позволяют предположить антирадикальний механизм противовоспалительной активности соединений данного ряда. Выводы. Установлено противовоспалительную и антирадикальную активности ряда тиопирано[2,3-d]тиазолов, идентифицировано соединения с высоким уровнем активности, а также проанализированы некоторые аспекты взаимосвязи структура-активность.